A clinical case of treatment of a reverse incisal overlap - S. N. Gromova; A. K. Koledaeva; P. A. Klimova; P. A. Lyapunova; A. A. Krivosheeva; V. A. Razumny; A. G. Kazakova; T. O. Zubareba (Эндодонтия Today, 2024)
The dental system formation depends on many factors, the inﬂuence of which is signiﬁcant at all stages of development. Most often, these factors have a complex eﬀect, it can be: genetic predisposition, environmental factors, bad habits and speciﬁc causes. Timely and eﬀective orthodontic treatment of developmental abnormalities of the dentofacial apparatus remains a pressing problem for both adults and children, since dentofacial anomalies are quite common in our time and have a pronounced tendency to progress.Among the clinical manifestations associated with occlusion pathology, reverse incisal overlap is not as widespread, but is the cause of the formation of functional and morphological disorders in the maxillofacial region and other body systems.Early diagnosis and correct treatment of this pathology contributes to the harmonious development of the oral cavity and also the entire human musculoskeletal system.